Evaluation of selected coated urea on nitrogen use efficiency of rice - Ahmad Khariri, Rosmarina (2016)
Urea is the main nitrogen (N) fertilizer sources applied in the rice production. However, the efficiency of urea in rice system is generally low. A part of applied N will be loss due to ammonia (NH3) volatilization, nitrification and denitrification. In order to minimize N losses, urea was coated with urease inhibitor, nitrification inhibitor, inorganic materials or supplemented with biochar. This study was carried out with the following objectives: to evaluate the effect of different coated urea on N transformation, NH3 volatilization, nitrous oxide (N2O) gas emissions in selected rice soils and rice production; to determine N utilization and the pattern of fertilizer N uptake by hybrid rice in comparison of inbred varieties. Copper (Cu) and zinc (Zn) acted as urease inhibitors and dimethylpyrazol-phosphate (DMPP) was selected as nitrification inhibitor. The N fertilizers compared were urea, Cu coated urea (CuU), Zn coated urea (ZnU), Cu + Zn coated urea (CuZn), DMPP coated urea (DMPPU), DMPP + Cu + Zn coated urea (DMPPCuZn), sulfur coated urea (SU), dolomite coated urea (DU) and OneBaja (urea impregnated biochar). Copper, Zn and DMPP coated urea were prepared by coating them with palm stearin. Laboratory evaluation of coated urea was conducted to measure N transformation, NH3 volatilization and N2O emission in Selangor and Chempaka soil. Results indicated that treatments consisting of urease inhibitor slowed urea hydrolysis. Copper coated urea, ZnU, CuZn, DMPPCuZn, SU, OneBaja were effective in reducing NH3 loss as compared to urea by 12.12 - 37.48%. Furthermore, SU, CuU, ZnU, CuZn, DMPPU and DMPPCuZn reduced N2O emission over urea by 14.86 - 48.65%. Glasshouse study was carried out to measure fertilizer N utilization and pattern of fertilizer N uptake by hybrid rice named Siraj in comparison to MR219 by using 15N isotopic label technique. Rice plants were harvested at two weeks interval starting from 2nd week (DAT-day after transplant) until 14th week. Fertilizer N uptake and utilization reached a peak between 10th and 12th week. Relatively, Siraj recorded better fertilizer N utilization and N uptake as compared to MR219 variety. A second glasshouse study was carried out to determine the effect of coated urea on rice yield. Siraj and MR220 variety were grown in one growing season in Selangor and Chempaka soil. Pots treated with OneBaja, CuU, ZnU, CuZn, DMPPU and DMPPCuZn showed an improvement of grain yield by 32.96 - 39.05% over urea in Chempaka soil. Higher grain yield was recorded in pots applied with CuU, CuZn, DMPPCuZn and SU as compared to urea in Selangor soil. Field study was conducted at Sungai Besar Selangor. The rice were directly seeded by manual broadcasting practice. Results demonstrated that, coated urea (CuU, CuZn, DMPPU, DMPPCuZn) and OneBaja treated plots produced better rice yield and N uptake with an increment of 17.43 - 28.44% and 20.72 - 42.28% respectively. Siraj outperformed MR220 in increasing grain yield and N uptake. This suggests that there is a prospect of using urease and nitrification inhibitor coated urea and OneBaja to improve N efficiency of urea and rice yield.